Methylation status and long‐fragment cell‐free DNA are prognostic biomarkers for gastric cancer - Kazuhide Ko; Yoshikazu Kananazawa; Takeshi Yamada; Daisuke Kakinuma; Kunihiko Matsuno; Fumihiko Ando; Sho Kuriyama; Akihisa Matsuda; Hiroshi Yoshida (Cancer Medicine, 2021)
Abstract Background Circulating tumor DNA (ctDNA) detected before surgery disappears after complete surgical resection of the cancer. Residual ctDNA indicates minimal residual disease (MRD), which is a cause of recurrence. The presence of long‐fragment circulating cell‐free DNA (cfDNA) or methylated cfDNA also implies the presence of cancer. In this study, we evaluated the prognostic value of cfDNA methylation and long‐fragment cfDNA concentration in gastric cancer patients undergoing curative surgery Methods Ninety‐nine gastric cancer patients were included. Peripheral blood samples were collected before and 1 month after surgery. In patients administered chemotherapy, samples were collected before starting chemotherapy. qPCR was performed to detect long‐ and short‐fragment LINE‐1. A plasma HELP (HpaII tiny fragment Enrichment by Ligation‐mediated PCR) assay to determine the concentration of HpaII small fragments was performed using ligation‐mediated PCR and HpaII was quantified as the HpaII:MspI ratio to detect methylation levels of cfDNA. Results Overall survival (OS) of patients with low methylation levels before starting treatment was significantly worse than that of patients with high methylation levels (P = 0.006). In the 90 patients who underwent curative surgery, recurrence‐free survival (RFS) and OS of patients with low methylation levels before surgery were worse than those with high methylation levels (P=0.08 and P = 0.11, respectively). RFS and OS of patients with high concentrations of long‐fragment LINE‐1 after surgery were significantly worse than those with low concentrations of long‐fragment LINE‐1 (P = 0.009, P = 0.04). Conclusions Pre‐surgical low methylation levels of LINE‐1 are a negative prognostic factor. Post‐surgical high concentrations of long‐fragment LINE‐1 indicate MRD and a high risk of recurrence.